Невідома перемога: перший значний епізод у кар’єрі І.Богуна - Таїрова-Яковлева, Т. (Український історичний журнал, 2021)
Мета дослідження полягає у висвітленні на основі архівних матеріалів
раніше невідомого епізоду з життя І.Богуна. Методологія базується на використанні
загальнонаукового, конкретно-історичного, а також порівняльного методів. Наукова новизна.
Уперше досліджується досі незнаний бій, що відбувся 1643 р. на Казанському перевозі через
р. Дон. Детально зображено його перебіг, причини, результати, а також роль у подіях І.Богуна.
Висновки. Бій на Казанському перевозі став найпершим із тих, що тепер відомі історичній
науці, у кар’єрі майбутнього козацького полководця. Тоді козаки під орудою І.Богуна розбили
загін донців і російських стрільців, котрі захищали «городок», що перешкоджав вільному
переходу через Дон. І.Богун у той час служив отаманом у фортеці Кодак і мав під своєю рукою
до 200 вояків. Він зарекомендував себе талановитим, відважним командиром, схильним до
рішучих, а то й зухвалих дій, швидких, нестандартних рішень. Перемога біля Казанського
перевозу принесла І.Богунові популярність у козацькому середовищі. Ця був перший випадок,
коли він застосував «фортель», що надалі стане його «фірмовим» стилем. Звитяга І.Богуна
викликала різку реакцію в Москві, спричинивши спеціальне розслідування. The aim of the research is to investigate the previously unknown I.Bohun’s young years
on the basis of documents from the Russian State Archive of Ancient Acts. The methodology is
based on general scientific and specific historical research methods, as well as the comparative method.
The scientific novelty is that for the first time, on the basis of archival documents, the unknown
fight of the famous Cossack commander I.Bohun, which took place in 1643 on the Kazan ferry of
the Don River, is described. The article details the course of the fight, the causes and results, as well
as the personal role of I.Bohun. Conclusions. The fight on the Kazan ferry of the Don River is the
very first battle of I.Bohun, which is now known to historical science. During the fight, a detachment
of Cossacks under the command of I.Bohun defeated a detachment of Don Cossacks and Russian
archers who defended the “town” which did not give free passage through the Don. I.Bohun at that
time was the otaman in the Kodak fortress and had 200 Cossacks under his command. I.Bohun has
shown himself as a talented, courageous and successful chieftain who dared to take decisive and daring
actions, did not lose his presence of mind in difficult combat situations and used quick, non-standard
solutions. The victory at the Kazan ferry, of course, brought I.Bohun fame, both among the security
forces and among the Cossacks. This fight is also the first time when I.Bohun used “trick”, which
later became his signature style. Bohun’s victory, the loss of more than 19 people by the Russians
caused a sharp reaction in Moscow and prompted an investigation at the highest level.